2018
DOI: 10.1159/000488015
|View full text |Cite
|
Sign up to set email alerts
|

IL-33 and Its Receptor ST2 after Inhaled Allergen Challenge in Allergic Asthmatics

Abstract: Background: Previous murine models have demonstrated interleukin (IL)-33 to be an important mediator of type-2 inflammation and to promote airway hyperresponsiveness in allergic asthma. A number of inflammatory cells produce IL-33 and eosinophils express ST2 mRNA. The relationship between IL-33 and eosinophils in allergic asthma, however, remains unclear. Objective: The aim of this work was to evaluate in vitro the effect of allergen inhalation on IL-33 levels and expression of its receptor (ST2L) on eosinophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 41 publications
1
27
0
Order By: Relevance
“…Why the IL‐33 level does not increase after allergen exposure remains a controversial issue. Although bronchial epithelial, smooth muscle and mast cells have been identified as key sources, the principal origin of IL‐33 in allergic disease is not fully known . One assumption may be made that elevated levels of soluble ST2 receptors for IL‐33 in AA suggest localized production of this soluble form of ST2 within the airways that may act as an inhibitor of IL‐33‐induced inflammation …”
Section: Discussionmentioning
confidence: 99%
“…Why the IL‐33 level does not increase after allergen exposure remains a controversial issue. Although bronchial epithelial, smooth muscle and mast cells have been identified as key sources, the principal origin of IL‐33 in allergic disease is not fully known . One assumption may be made that elevated levels of soluble ST2 receptors for IL‐33 in AA suggest localized production of this soluble form of ST2 within the airways that may act as an inhibitor of IL‐33‐induced inflammation …”
Section: Discussionmentioning
confidence: 99%
“…There is substantial evidence that the alarmins, TSLP and IL-33, play key roles in driving T2 inflammation in asthma. TSLP levels in bronchial lavage fluid and biopsies are elevated in patients with asthma compared with healthy individuals, and correlate with disease severity (including a negative correlation with lung function defined by forced expiratory volume in 1 second [FEV 1 ]) [54][55][56][57]. In addition, genetic studies of TSLP have identified alleles that are associated with asthma [58].…”
Section: Role Of Tslp and Il-33 In T2-high Asthmamentioning
confidence: 99%
“…Additionally, patients with allergic and eosinophilic asthma phenotypes have higher serum levels of IL-33 than those with non-allergic and non-eosinophilic phenotypes [62]. Furthermore, in patients with allergic asthma, ST2 expression on eosinophils from blood and sputum is significantly upregulated after allergen inhalation challenge [54]. Higher serum soluble ST2 levels are associated with an increased risk of exacerbations [63].…”
Section: Role Of Tslp and Il-33 In T2-high Asthmamentioning
confidence: 99%
See 1 more Smart Citation
“…In order to classify asthma patients and assign them to specific, targeted therapies, biomarkers, and biomarker profiles – for example cytokines involved in asthma pathogenesis – periostin as a marker of eosinophilic inflammation that is IgE specific to certain allergens has become very important [4]. Furthermore, the expression of the interleukin (IL)-33 receptor ST2L on eosinophils, which increases significantly at 24 h postallergen inhalation in allergic asthmatics, might serve as a biomarker and is considered a therapeutic target for asthma [5]. The presence and levels of epithelium-derived cytokines in exhaled-breath condensate have been studied in patients with chronic asthma in order to identify biomarkers for asthma severity.…”
Section: Toward New Therapies For Asthmamentioning
confidence: 99%